RETRACTED: Expression of Concern: The Turnaway Study: A Case of Self-Correction in Science Upended by Political Motivation and Unvetted Findings - Coleman, Priscilla K. (Frontiers in Psychology, 2022)
This review begins with a detailed focus on the Turnaway Study, which addresses associations among early abortion, later abortion, and denied abortion relative to various outcomes including mental health indicators. The Turnaway Study was comprised of 516 women; however, an exact percentage of the population is not discernable due to missing information. Extrapolating from what is known reveals a likely low of 0.32% to a maximum of 3.18% of participants sampled from the available the pool. Motivation for conducting the Turnaway Study, methodological deficiencies (sampling issues and others), and bias are specifically addressed. Despite serious departures from accepted scientific practices, journals in psychology and medicine have published dozens of articles generated from the study’s data. The high volume of one-sided publications has stifled dialogue on potential adverse psychological consequences of this common procedure. Following a critical analysis of the Turnaway Study, an overview of the strongest studies on abortion and mental health is offered. This comprehensive literature comprised of numerous large-scale studies from across the globe has been largely overlooked by scientists and the public, while the Turnaway Study dominates the media, information provided to women, and legal challenges involving abortion restrictions. In the final section of this article, literature reviews by professional organizations are considered, demonstrating that the biased science characterizing the Turnaway Study is aligned with a pervasive and systemic phenomenon wherein deriving reliable and valid results via careful attention to methodology and scrutiny by the scientific community have been supplanted by politics.